FAKTOR-FAKTOR YANG MEMPENGARUHI INTENSI UNTUK MELAKUKAN WHISTLEBLOWING INTERNAL PADA OPD DI KABUPATEN SUMENEP - Arief Hidayatullah Khamainy; Moh Faisol (JURNAL RISET TERAPAN AKUNTANSI, 2021)
The practice of whistleblowing is very important, but in fact the intention to carry out this practice is still rare in Indonesia because someone who is supposed to be a whistleblower prefers to be silent rather than having to report fraud in the hope that they feel more secure in their position if they do not carry out this practice, whistleblowing practice is needed to reveal the existence of fraud in an organization. This study aims to analyze and examine the factors that influence the intention to conduct internal whistleblowing at OPD in Sumenep Regency. These factors are relativism ethical orientation, moral intensity, organizational commitment and professional identity. Quantitative methods are used in this research. The data process is by using the survey method. The population used in this study were all OPDs of Sumenep Regency which connected 25 OPDs. The sample selection in the study used a saturated sampling method. The data analysis in this study used multiple linear regression with the SPSS version 20 program. The results showed that all factors used in this study were factors that encouraged a person “to carry out internal whistleblowing intentions, so that all hypotheses in this study were accepted.